2015
DOI: 10.1080/08912963.2015.1049948
|View full text |Cite
|
Sign up to set email alerts
|

Turiasauria-like teeth from the Upper Jurassic of the Lusitanian Basin, Portugal

Abstract: Turiasauria is a clade of eusauropods with a wide stratigraphic range that could extend from the Bathonian to the lower Aptian including Turiasaurus, Losillasaurus, Zby and putatively, Galveosaurus, Atlasaurus and isolated remains from Middle Jurassic-to-Lower Cretaceous. Some are characterised by the presence of heart-shaped teeth. Several tooth occurrences from the Portuguese Upper Jurassic with this type of morphology (SI: 1.1-1.8) are reported and discussed. If this morphology is regarded as synapomorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 67 publications
(94 reference statements)
1
61
0
Order By: Relevance
“…The known and the new occurrences put in evindece a relatively high potential for future dis-12 coveries in this area, However, the so far published (Mocho et al, 2012(Mocho et al, , 2016b and unpublished material of sauropods only allows identification of indeterminate sauropods and eusauropods, possibly members of Turiasauria, and indeterminate macronarians. The presence of several compressed cone-chisel teeth in the sedimentary sequence suggests the presence of macronarian forms within the clade formed by Europasaurus + Titanosauriformes (Figure 6.2).…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…The known and the new occurrences put in evindece a relatively high potential for future dis-12 coveries in this area, However, the so far published (Mocho et al, 2012(Mocho et al, , 2016b and unpublished material of sauropods only allows identification of indeterminate sauropods and eusauropods, possibly members of Turiasauria, and indeterminate macronarians. The presence of several compressed cone-chisel teeth in the sedimentary sequence suggests the presence of macronarian forms within the clade formed by Europasaurus + Titanosauriformes (Figure 6.2).…”
Section: Figurementioning
confidence: 99%
“…This new information suggests a more diverse scenario for sauropod fauna during the Late Jurassic of the Lusitanian Basin than previously considered, with the identification of a clade previously unidentified in this basin, the non-neosauropod eusauropod group Turiasauria. Royo-Torres et al (2006) suggested the presence of Turiasauria in the Portuguese Upper Jurassic record, and this hypothesis was subsequently corroborated by the presence of new teeth and postcranial material (Mateus, 2009;Royo-Torres et al, 2009;Ortega et al, 2010;Mocho et al, 2012;Royo-Torres et al, 2014a;Mocho et al, 2016b). Four taxa, so far exclusively, were described in the Upper Jurassic of the Lusitanian Basin: the camarasaurid Lourinhasaurus alenquerensis (Lapparent and Zbyszewski, 1957;Dantas et al, 1998;Mocho et al, 2014b); the diplodocid Dinheirosaurus lourinhanensis (Bonaparte and Mateus, 1999;Mannion et al, 2012; recently referred as Supersaurus lourinhanensis by Tschopp et al, 2015), the basal macronarian and putative brachiosaurid Lusotitan atalaiensis (Lapparent and Zbyszewski, 1957;Antunes and Mateus, 2003;Mannion et al, 2013), and the turiasaur Zby atlanticus .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations